Respuesta agronómica de las variedades de arroz ‘s – fl – 09’ y ‘f – 21’ a diferentes dosis y épocas de aplicación del promotor de crecimiento a base de extracto de algas marina ‘fartum - Paredes Monar, Ángel Félix (2011)
On the grounds of the Hda. 'Aurora', located at Km 31, route Duran - Naranjal, a trial was conducted in two varieties of rice in the presence of various doses and times of application of a growth promoter, in order to evaluate the agronomic and yield response grain varieties 'S - FL - 09' and 'F - 21', to identify the appropriate dose and time of application of fartum to maximize grain yield, determine the efficiency of growth promoter and economic analysis of performance grain according to the cost of treatments. The dose and timing of application of fartum were: 3.0, 4.5 and 6.0 l / ha split into three equal parts and applied at the beginning of tillering, stem elongation and initiation of floral primordia, 3.0, 4.5 and 6.0 l / ha fartum fractionated two equal parts and applied at the beginning of tillering and stem elongation. In addition, we included a control treatment lacking the fartum.........